Synthesis and Photocatalytic Performance Evaluation of BaTiO3/ZnO/Cs3Bi2I9 Based Perovskite for Solar Cell Applications - Allawi Kadhim, Hala; Majida Hameed Khazaal (Malaysian Journal of Science (MJS), 2025)
Due to the light absorption properties of perovskites, including halides, perovskite cells are considered an ideal energy system. This study aims to improve photoexcitation separation by introducing a material with a perovskite-like structure, such as Cs3Bi2I9, alone or with barium titanate nanoparticles as a second choice, while the third choice is to impregnate barium titanate (prepared by hydrothermal method) with ZnO to form BaTiO3/ZnO, then mix it with Cs3Bi2I9. All these choices are fabricated as a sandwich between the n-type and p-type collection. The produced layers, BaTiO3/ZnO /Cs3Bi2I9, were characterized using XRD, EDX, SEM, and UV-Vis spectroscopic analytical techniques. The results suggest that the band gap of the prepared layer was further decreased compared to the original material, Cs3Bi2I9. The performance test revealed a photo conversion efficiency (PCE) of 3.13% and a highest power of 3.15 MW, comparable to or higher than other studies. This suggests that this layer significantly reduces recombination phenomena and improves the cell’s performance overall.